Social partnering alters sleep in fear-conditioned Wistar rats - DaSilva, Jamie K.; Husain, Eram; Lei, Yanlin; Mann, Graziella L.; Morrison, Adrian R.; Tejani-Butt, Shanaz (PLOS ONE, 2017)
Social support, when provided following a traumatic experience, is associated with a lower incidence of stress-related psychiatric disorders. Our hypothesis was that providing a social interaction period with a naive conspecific would improve sleep architecture in response to cued fear conditioning in Wistar rats. Rats were randomly assigned to either the socially isolated or socially partnered groups. Rats assigned to the socially isolated group were individually housed following electrode implantation and fear conditioning. Rats assigned to the socially partnered group were initially paired-housed, and then one rat from each pair was randomly chosen for sleep electrode implantation and fear conditioning. Rats from both groups were habituated to a recording chamber, and baseline sleep was recorded over 22 hours. One day later (Training Day), they were fear-conditioned to 10 presentations of a tone (800 Hz, 90 dB, 5 sec) co-terminating with a mild electric foot shock (1.0 mA, 0.5 sec), at 30-sec intervals. While rats in the socially isolated group were left undisturbed in their home cage for 30-min, socially partnered rats interacted for 30 minutes with their non-stressed rat partner immediately after fear conditioning and while the auditory tones were presented on Days 1 and 14. The results indicated that social interaction increased sleep efficiency in partnered rats compared to isolated rats following the fear conditioning procedure. This was due to an increase in the amount of rapid eye movement sleep (REMS) during the light phase. Evaluation of REMS microarchitecture revealed that the increase in REMS was due to an increase in the number of single REMS episodes (siREMS), which represented a more consolidated REMS pattern. A surprising finding was that partnered rats had a greater number of sequential REMS episodes (seqREMS) at Baseline, on the Training Day and on Day 1 when compared to isolated rats. The greater number of seqREMS episodes in partnered rats may be due to the partnering procedure and not fear conditioning, as the effect was also seen at Baseline. Thus it appears that while the partnering procedure may have given rise to a fragmented REMS pattern, social partnering promoted a greater consolidation of REMS in response to the fear conditioning procedure.